The mechanisms of the semiotics of passions and their manifestations in modern Iraqi poetry(Ali Al-Sharqi) - Ali Abdul Raheem Kareem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
In his book "Emotions and Storms" issued in Baghdad in 1952, the Iraqi poet Sheikh Ali al-Sharqi 1894-1964 distinguishes himself from his peers among the poets of his time, and from the poets who followed him in dealing with emotional states in their subject matter and style. The poet tries to deal with human concerns, portraying his troubled, persecuted self, who found himself imprisoned in a prison, until he became a nightmare suspended in a cage, and seemed to suffer from the theft of happiness, and live in confusion and loss. Thus, the poet continues to reveal various emotional states. In this research, an attempt is made to apply the various mechanisms and procedures adopted by the semiotics of the passions of Grimas and Fontane in their book (The Semiotics of the Passions from the States of Things to the States of the Soul, 1991). This research also benefits from the readings of J. K. Cookie in his book (The Pursuit of Meaning, 1997), and is interested in the views of Dennis Bert Arn in his book (Literary Semiotics, 2000). This research reveals the connotations carried by the passions in the poems of Al-Sharqi, showing the mechanisms of action of emotions and how to produce their meanings, as well as monitoring the extent of the influence of these emotions in the formation of different connotations. This research pays attention to emotions, ways of achieving them, and clarifying their ability to generate hidden tendencies, which constitute an entry point for identifying emotional states that the self shows before the significance is formed in the cognitive and deliberative dimensions.